Pharmacognostic, Phytochemical, Antimicrobial and Antioxidant Activity Evaluation of Amaranthus tricolor Linn. Leaf - Tharun; Nagavenkateshwar Rao, Korlepara; Krushna Padhy, Sai; Kumar Dinakaran, Sathis; Banji, David; Avasarala, Harani; Ghosh, Somsubhra; Sravan Prasad, Macharla (Asian Journal of Chemistry, 2011)
The study is aimed to investigate the pharmacognostic, phytochemical, antimicrobial screening and antioxidant activity of different extracts of Amaranthus tricolor with a view of justifying the use of the plant. The test tube reactions and TLC examination revealed the presence of phenols, tannins and flavonoids in chloroform, ethanolic and aqueous extracts of A. tricolor. By present work, it is concluded that the plant A. tricolor is endowed with significant antimicrobial and antioxidant activity due to the presence active constituents like polyphenolic conents and others, thus justifying its use in the indigenous system of medicine. The results of organoleptic, microscopical and physical evaluation were satisfactory and can be correlated with earlier reports.